Contestation of Religious Identity in the Cultural Heritage Sites: A Case Study of the Masjid Gedhe Kauman Yogyakarta, Indonesia - Fahmi Prihantoro; Irham Wibowo; Adieyatna Fajri; Ghifari Yuristiadhi Masyhari Makhasi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This article explores the contestation of religious identity at the Masjid Gedhe ‘Grand Mosque’ of Kauman Yogyakarta, a provincial cultural heritage site in Yogyakarta. The study focuses on two events between October 2019 and March 2020: the rejection of the Muslim United #2 event by the Keraton ‘Palace’ and the refusal by the local Kauman community to hold a Nahdhatul Ulama anniversary at the mosque. The series of events can be read as an effort by each party to contest the power they have. This research is a descriptive study guided by a constructivist research philosophy and historical approach, which focuses on understanding cultural identity through the lens of social context. The study employs a combination of primary sources, such as photo archives and documents, alongside secondary sources, including articles from online news portals, to analyze two specific events. Data is collected through these sources and analyzed using Stuart Hall's cultural identity theory, providing a framework for interpreting the findings and examining how religious identity is contested at the Masjid Gedhe Kauman Yogyakarta. The result highlights how the Masjid Gedhe Kauman Yogyakarta became a contested space for religious identity between different groups, with each event reflecting ongoing power dynamics and cultural negotiations. The rejection of both the Muslim United #2 and the NU Anniversary events illustrates how identity is shaped and contested through representation and authority, where power structures, both institutional and community-based, played key roles in defining the mosque's religious and cultural identity.